Penambahan Fly Ash dan Bottom Ash Pada Tanah Lempung Lunak Sebagai Bahan Stabilisasi Terhadap Uji Sifat Mekanis Tanah Untuk Peningkatan Nilai CBR - Rani Nurul Wijayanti; Rachmat Mudiyono; Abdul Rochim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In recent years, the development of road infrastructure in Indonesia has shown quite rapid progress. However, this process often faces technical obstacles, especially those related to the condition of the subgrade which has low bearing capacity. This type of soil condition requires a stabilization process so that the California Bearing Ratio (CBR) value of the soil can increase so that it meets the strength standards required to support durable road construction. In relation to efforts to improve the characteristics of soft clay soil in the Semarang area, a study utilized coal combustion waste in the form of fly ash and bottom ash from the Tanjung Jati B Steam Power Plant (PLTU). This alternative material is used to improve the quality of the soil so that it is more technically feasible for various construction needs. Through a series of laboratory tests with variations in the composition of the fly ash mixture between 15% to 45% and bottom ash between 15% to 25%, a significant increase in the CBR value was obtained compared to the original soil without treatment. The best composition obtained in this study consisted of 40% soil, 45% fly ash, and 15% bottom ash, with a CBR value reaching 8.95%. These findings indicate that coal combustion waste has great potential in improving the quality of the subgrade. The use of this material can be a cost-efficient and environmentally friendly alternative in the construction of road infrastructure